Optimasi Metode Ekstraksi Microwave Assisted Extraction Biji Markisa (Passiflora edulis Sims) terhadap Aktivitas Antioksidan - Virsa Handayani; Muh. Alif Noor Fauzan; Alifah Rifa Nadya; Harti Widiastuti; Abd. Malik; Aktsar Roskiana Ahmad (Pengurus Pusat Ikatan Apoteker Indonesia, 2025)
Passion fruit (Passiflora edulis Sims) is a trailing plant of non-native origin, belonging to the genus Passiflora. The utilisation of purple passion fruit seeds (Passiflora edulis Sims) has been extensively documented in traditional medicine. These seeds have been employed in various therapeutic applications, including antioxidant, anti-inflammatory, antipyretic, analgesic and hypotensive properties. The objective of the present study was to ascertain the potential for enhancing the antioxidant activity of passion fruit seed oil (Passiflora edulis Sims) through 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical-scavenging method. The extraction method used was Microwave Assisted Extraction (MAE) utilising n-Hexane as a solvent, with variations in temperature and time. The results obtained for passion fruit seed oil at low temperature (20°C) revealed an IC50 of 14.58 µg/mL after 10 minutes and 7.144 µg/mL after 20 minutes. At medium-low temperature (36°C), the IC50 was 4.67 µg/mL after 10 minutes and 2.68 µg/mL after 20 minutes. At medium temperature (95°C), the IC50 was 4.46 µg/mL after 10 minutes and 2.26 µg/mL after 20 minutes.